Technological Revolutions and Financial Capital: The Dynamics of Bubbl es and Golden Ages - Perez, Carlota (Edward Elgar Publishing Ltd, 2003)
Technological Revolutions and Financial Capital presents a novel inter pretation of the good and bad times in the economy, taking a long-term perspective and linking technology and finance in an original and con vincing way. Carlota Perez draws upon Schumpeter's theories of the clu stering of innovations to explain why each technological revolution gi ves rise to a paradigm shift and a 'New Economy' and how these 'opport unity explosions', focused on specific industries, also lead to the re currence of financial bubbles and crises. These findings are illustrat ed with examples from the past two centuries: the industrial revolutio n, the age of steam and railways, the age of steel and electricity, th e emergence of mass production and automobiles, and the current inform ation revolution/knowledge society. By analyzing the changing relation ship between finance capital and production capital during the emergen ce, diffusion and assimilation of new technologies throughout the glob al economic system, this seminal book sheds new light on some of the m ost pressing economic problems of today. A bold interpretation of how the changing relationship between technological advances and financial capital shapes the patterns of economic cycles, this path-breaking bo ok will provide essential insights for business leaders, policymakers, academics and others concerned with managing change in the world econ omy.